STEM-23. LncRNA HOTAIR SPONGES miR301a-3p TO PROMOTE GLIOMA'S PROLIFERATION AND INVASION THROUGH THE ACTIVATION OF FosL1. (12th November 2021) - King, Pendelton; Guo, Alyssa; Wan, Jingwei; Liu, Mingli
Abstract: BACKGROUND: Non-coding RNAs, including LncRNAs, function in regulating glioblastomas' numerous oncogenic phenotypes, such as invasiveness and stemness of glioblastoma stem cells. These LncRNAs contain long non-encoding RNA transcripts >200 nucleotides in length, many of which show cell type-specific expression. In this project, we investigated how TRPM7, a promoter for glioma's proliferation and invasion, regulates LncRNA and contributes to glioma tumorigenesis. METHODS: 1) Total RNA, from either with A172 glioma cells or A172 glioma cells with TRPM7 knocked out (A172 KO), were extracted and then parallelly subjected to Human Cancer Pathway Finder, RT2 LncRNA PCR Array. 2) We then analyzed the prognostic role of LncRNAs using a publicly available bioinformatics data set (www.Oncolanc.org ). 3) We examined the effects of TRPM7-regulated LncRNA, and its downstream molecules miR301a-3p and FosL1 oncogene, on the proliferation and invasion of glioma cells in A172 and PDX-L12 cells by either inhibition or activation of the above molecules. RESULTS: 1) Data analysis from RT 2 data resulted in a list of 10 downregulated and 7 upregulated LncRNAs whose transcripts are statistically significant with fold changes greater than 2.0 by TRPM7 knockout. 2) The results showed that TRPM7 functions as a positive regulator of LncRNA, HOTAIR, which is an unfavorable prognostic factor of 7-year overall survival in glioma patients. 3) In addition, we found that LncRNA HOTAIR sponges miR-301a-3p to promote proliferation, invasion, and stemness of glioma through upregulating the oncogene FosL1. 4) Furthermore, we identified that FosL1 is a novel prognostic marker of glioma patients. CONCLUSION: Our results demonstrated the role of TRPM7-regulated LncRNA HOTAIR as a miRNA sponge in glioma, which shed new light on LncRNA-directed therapeutics in glioma.